2010
DOI: 10.1080/10256010903388410
|View full text |Cite
|
Sign up to set email alerts
|

Influence of forage preferences and habitat use on13C and15N abundance in wild caribou (Rangifer tarandus caribou) and moose (Alces alces) from Canada

Abstract: Stable isotope composition (delta(13)C and delta(15)N) of moose (Alces alces) and caribou (Rangifer tarandus) hair from the boreal forest of Jacques-Cartier Park and Cote-Nord (Quebec) and arctic tundra of Queen Maud Gulf and Southampton Island (Nunavut) was investigated as an indicator of dietary preferences and habitat use. Values of delta(13)C(hair) and delta(15)N(hair) in moose were consistently lower compared to those of caribou. This is consistent with the depletion in (13)C and (15)N in the plants prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 42 publications
9
55
1
2
Order By: Relevance
“…The increasing order of δ 13 C values from moose to mountain caribou corresponds with the patterns observed for a summer diet in the same species in Alaska (Ben-David et al, 2001) and eastern Canada (Drucker et al, 2010). Isotopic ratios from individual plant species are not available for this study, but the observed difference in the ratios are likely due to the lower consumption of tree and shrub buds and leaves and the greater quantity of lichen in the caribou diet.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The increasing order of δ 13 C values from moose to mountain caribou corresponds with the patterns observed for a summer diet in the same species in Alaska (Ben-David et al, 2001) and eastern Canada (Drucker et al, 2010). Isotopic ratios from individual plant species are not available for this study, but the observed difference in the ratios are likely due to the lower consumption of tree and shrub buds and leaves and the greater quantity of lichen in the caribou diet.…”
Section: Discussionsupporting
confidence: 58%
“…These isotopic differences occur despite the exclusive presence of C 3 plants in the Arctic environment (Drucker et al, 2010). 15 N is generally used to define the trophic position of a species (Kelly, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates the absence of a 'canopy' depleted signature. Two alternative hypotheses can be suggested: This reproduces to some extent recent debate regarding cervid species from the northern hemisphere (Stevens et al, 2006;Drucker et al, 2008Drucker et al, , 2010. Information available for guanacos is relevant for this issue (Barberena et al, , 2010Tessone, 2010) since, based on relatively large sample sizes, steppe guanacos can be statistically differentiated from forest guanacos, which would display an incidence of the canopy effect (Table 4, Fig.…”
Section: Ccollagen: Canopy Effect On Temperate Forestsmentioning
confidence: 80%
“…At face value, these findings can be seen as incompatible. Nevertheless, C and N biochemical cycles are conditioned by different regulating factors (Ambrose, 1991;van der Merwe and Medina, 1991;Cormie and Schwarcz et al, 1996;Ehleringer and Cerling, 2001;Drucker et al, 2008Drucker et al, , 2010Craine et al, 2009;Ugan and Coltrain, 2011), not completely understood yet, and may not vary in conjunction. The zooarchaeological record from the western Patagonian forests indicates that human groups inhabiting the area regularly hunted and consumed huemul (Mena, 1983;Belardi and Gómez Otero, 1998;De Nigris, 2004;Mena et al, 2004;Méndez et al, 2006;Fernández, 2010).…”
Section: Conclusion and Implications For Human Paleodietary Studiesmentioning
confidence: 97%
“…This variability might prove an opportunity, however, in that it could enable seasonal adaptation in prehistory to be identified using carbon, nitrogen and oxygen isotopes of archaeological faunal and human teeth and bones (e.g. Balasse et al, 2009;Drucker et al, 2010;Gröcke et al, 1997).…”
mentioning
confidence: 99%